Reversed Phase HPLC Studies on the Change of the Free Amino Acid Content of Tobacco During Ageing - Ming, Ning-Ning; Jin, Xiao-Yan; Qiang, Liu; Yong, Su; Guo, Jun-Cheng (Asian Journal of Chemistry, 2010)
Tobacco leaf samples from different leaf positions, different ageing times were extracted for the determination of free amino acid. The analysis methods involve cation exchange extraction and reversed phase HPLC using a pre-column derivatization with 6-aminoquinoyl- N-hydroxysuccinimidyl carbamate (AQC). The method is suited for the separation of most free amino acids. It allows high recovery and satisfies the necessary requirements with respect to accuracy, repeatability and sensitivity. Seventeen amino acids were unequivocally identified, including aspartate, serine, glutamate, etc. The results shows that free amino acid concentrations decrease with increasing ageing time and vary with leaf position.